Pengaruh Stress Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan di PT Buana Finance Cabang Alam Sutera - Herdiansyah, Irwan; Hidayat, Arif; Saputra, Allyya (Pascasarjana STIE Amkop Makassar, 2024)
This research aims to identify and analyze the influence of work stress and the work environment on employee performance at PT. Buana Finance Alam Sutera Branch. Using a quantitative approach, data was collected through a survey of employees and analyzed using multiple regression. The objectives of this research are: (1) to determine the level of work stress at PT. Buana Finance Alam Sutera Branch; (2) to determine the quality of the work environment at PT. Buana Finance Alam Sutera Branch; (3) to evaluate employee performance at PT. Buana Finance Alam Sutera Branch; (4) to determine the influence of work stress on employee performance; (5) to determine the influence of the work environment on employee performance; and (6) to evaluate the simultaneous influence of work stress and work environment on employee performance. The research results show that work stress and the work environment have a significant influence on employee performance. The multiple regression test obtained an R value of 0.883 and an R square of 0.779, which indicates that 76.8% of the variation in employee performance can be explained by these two variables. The F test shows that these two variables simultaneously have a significant effect on employee performance, while the partial test shows the significant influence of each variable. It is recommended that PT. Buana Finance develops stress management programs and improves the quality of the work environment to support optimal performance.